Constitutive analysis of Cu-DHP alloy during hot compression - Kalhor, Alireza; Rodak, Kinga; Maleki, Milad; Sohrabi, Mohammad Javad; Mobasheri, Mohammad; Mirzadeh, Hamed; Habibi Parsa, Mohammad (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
The hot deformation behavior of the deoxidized high-phosphorus copper (Cu-DHP) was investigated during compressive deformation at a wide deformation temperature range of 200 to 1000 °C and strain rates ranging from 0.0005 to 0.4 s-1. The flow curves related to the hot working regime (500 to 1000 °C) generally showed distinct peak stresses with the fall of flow stress after the peak point, revealing the occurrence of dynamic recrystallization (DRX). By increasing the Zener-Hollomon parameter, the cyclic flow curves were replaced by the single-peak ones, and finally by the characteristic dynamic recovery (DRV) curves. At temperatures lower than half of the melting point, only DRV-type curves were observed. Based on the constitutive analysis, the apparent activation energy of 274.1 kJ/mol, hyperbolic sine power of 4.88, and power law stress exponent of 5.27 were obtained, resulting in the flow stress equations to describe material flow in the hot working regime. The power law breakdown and the importance of deformation temperature were also critically discussed based on mathematical fitting, strain rate sensitivity index, and microstructural analysis.